2018
DOI: 10.1007/s00248-018-1223-z
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Enrichment Alters Salt Marsh Fungal Communities and Promotes Putative Fungal Denitrifiers

Abstract: Enrichment of ecosystems with excess nutrients is occurring at an alarming rate and has fundamentally altered ecosystems worldwide. Salt marshes, which lie at the land-sea interface, are highly effective at removing anthropogenic nutrients through the action of macrophytes and through microbial processes in coastal sediments. The response of salt marsh bacteria to excess nitrogen has been documented; however, the role of fungi and their response to excess nitrogen in salt marsh sediments is not fully understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 85 publications
0
19
0
Order By: Relevance
“…Greater availability of NO 3 − could potentially diminish the carbon storage capacity of salt marsh sediments as NO 3 − is an energetically favorable electron acceptor compared to sulfate (SO 4 2− ), and hence stimulates subsurface microbial respiration where OM is oxidized to fuel heterotrophic processes (Bulseco et al ). A number of studies have documented how microbes respond to increased NO 3 − supply, either through shifts in the active bacterial community (Kearns et al ), increased diversity and abundance of putative fungal denitrifiers (Kearns et al ), or increased functional potential for denitrification (Graves et al ). Several studies have also observed changes to ecosystem function in response to NO 3 − , including increased rates of denitrification and dissimilatory NO 3 − reduction to ammonium (DNRA; Koop‐Jakobsen and Giblin ).…”
mentioning
confidence: 99%
“…Greater availability of NO 3 − could potentially diminish the carbon storage capacity of salt marsh sediments as NO 3 − is an energetically favorable electron acceptor compared to sulfate (SO 4 2− ), and hence stimulates subsurface microbial respiration where OM is oxidized to fuel heterotrophic processes (Bulseco et al ). A number of studies have documented how microbes respond to increased NO 3 − supply, either through shifts in the active bacterial community (Kearns et al ), increased diversity and abundance of putative fungal denitrifiers (Kearns et al ), or increased functional potential for denitrification (Graves et al ). Several studies have also observed changes to ecosystem function in response to NO 3 − , including increased rates of denitrification and dissimilatory NO 3 − reduction to ammonium (DNRA; Koop‐Jakobsen and Giblin ).…”
mentioning
confidence: 99%
“…Both Cellvibrio and Chaetomium are commonly more abundant in tilled versus untilled fields ( Figure S9) [77][78][79][80] and, the latter in disturbed forest soils [81]. The occurrence of Chaetomium in agroecosystems may be linked to nitrogen fertilization, given their enrichment in Nfertilized fields and wetlands [82][83][84]. The predominance of these ruderal cellulolytic taxa is indicative of the frequent soil disturbances in agroecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…However, reduced nutrient inputs to coastal ecosystems could benefit C sequestration, as nutrient additions can result in net C loss through plant mortality, erosion, efflux, and remineralization via enhanced microbial activity (Macreadie et al, 2017b). Further, excess N has been linked to enhanced decomposition and an overall increase in tidal marsh ecosystem respiration due to shifts in microbial communities (Kearns et al, 2018).…”
Section: Introductionmentioning
confidence: 99%